Analysis of experts` quantitative assessment of adolescent basketball players and the role of anthropometric and physiological attributes - Strumbelj, E.; Erculj, F. (Journal of Human Kinetics, 2014)
In this paper, we investigated two questions: (1) can measurements of anthropometric and physiological attributes substitute for expert assessment of adolescent basketball players, and (2) how much does the quantitative assessment of a player vary among experts? The first question is relevant to the potential simplification of the player selection process. The second question pertains directly to the validity of expert quantitative assessment. Our research was based on data from 148 U14 female and male basketball players. For each player, an array of anthropometric and physiological attributes was recorded, including body height, body mass, BMI, and several motor skill tests. Furthermore, each player's current ability and potential ability were quantitatively evaluated by two different experts from a group of seven experts. Analysis of the recorded data showed that the anthropometric and physiological attributes explained between 15% and 40% of the variance in experts` scores. The primary predictive attributes were speed and agility (for predicting current ability) and body height and growth potential (for predicting potential ability). We concluded that these attributes were not sufficiently informative to act as a substitute for expert assessment of the players` current or potential ability. There is substantial variability in different experts' scores of the same player`s ability. However, the differences between experts are mostly in scale, and the relationships between experts` scores are monotonic. That is, different experts rank players on ability very similarly, but their scores are not well calibrated.